AB1339 Similar disease activity levels in US and turkish RA patients despite more biologic and methotrexate use in the US than turkey. (23rd January 2014) - Simsek, I.; Inanc, N.; Hatemi, G.; Pay, S.; Erdem, H.; Yilmaz, S.; Cinar, M.; Can, M.; Tascilar, K.; Ugurlu, S.; Cakir, N.; McCracken, W.A.; et al.
Abstract : Background: Real world applicability of "treat to target" approaches can only be assessed by routine care registries with different patient population and drug use. This also allows comparing RA treatment across different countries and provides insights previously not recognized. TRAV (Turkish acronym for "Turkish Rheumatoid Arthritis Registry") was established in 2010 with the aim of collecting data on RA patients seen in routine care in Turkey, the first consecutive patients database to do so. Objectives: To describe the current treatment paradigm and response to treatment among RA patients in Turkey and compare to a US cohort. Methods: Consecutive patients seen at participating centers complete at each visit a MDHAQ which includes scales for physical function, pain, and patient global. Physicians complete global assessment VAS, in addition to tender and swollen joint counts. RAPID3 (routine assessment of patient index data), DAS28 and CDAI are calculated. Demographics, self-reported disease activity measures, clinic data and medication usage were abstracted from the last visit of individuals with RA seen at three Turkish sites. Differences in measures from Turkey (TR) and an academic US site where similar data collection has been part of routine care were compared for status of biologic medication usage at last visit, abstracted from the same calendar treatment period. Significant differences in measures were determined using the Kruskal-Wallis test for continuous and ordinal measures and Chi-square test for categorical measures. Results: 899 RA patients in TR and 396 in the US were analyzed. There were significant differences between TR and US patients for years of education (TR=6.9 yr, US=14.5 yr) and disease duration (TR=14 yr, US=7.3 yr). Mean disease activity as measured by RAPID3 were similar between the sites (TR=10.5, US=11.2), with similar percentages of patients in remission, LDAS, moderate and high disease activity (TR=21%, 13%, 25%, 41%, and US=19%, 11%, 24%, 46%, respectively) at last visit. Only differences among the ACR core dataset measures were less swollen joints and MD global assessment scores in the US vs TR. 35% of US vs 22% of TR patients were on biologics (p<0.001), as were more patients on MTX in the US (54% vs 49%, p=0.01). Significantly more leflunomide and sulfasalazine were used in TR. Conclusions: Turkish and US RA patients had similar disease activity levels in composite indices, despite more biologic and MTX use in the US, however leflunomide and sulfasalasine were used more often in Turkey. On the other hand, US patients had lower swollen joint counts and MD global assessment of disease activity. The implications of the similarities and specific differences in some of the disease activity parameters in the long run, which is only possible by evaluating through real world registries are yet to be determined. Acknowledgements: The authors would like to thanks Cortex for their help with data entry and Bristol-Myers Squibb for unrestricted data entry support. Disclosure of Interest: I. Simsek: None Declared, N. Inanc: None Declared, G. Hatemi: None Declared, S. Pay: None Declared, H. Erdem: None Declared, S. Yilmaz: None Declared, M. Cinar: None Declared, M. Can: None Declared, K. Tascilar: None Declared, S. Ugurlu: None Declared, N. Cakir: None Declared, W. McCracken: None Declared, C. Swearingen: None Declared, H. Direskeneli: None Declared, Y. Yazici Grant/Research support from: Abbott, BMS, Celgene, Genentech, Consultant for: Abbott, BMS, Centocor, Celgene, Pfizer, genentech, UCB, Takeda